2022
DOI: 10.3390/healthcare10122533
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exercise Training Intensity on Physiological Adaptations and Insulin Resistance in Women with Abdominal Obesity

Abstract: Abdominal obesity has emerged globally as a major public health issue due to its high prevalence and morbidity. The benefits of physical exercise among the obese population are well documented. However, the optimal exercise intensity for reducing body fat and preventing insulin resistance and metabolic disorders is still under debate. This study aimed to examine the effects of three different intensities of combined endurance and strength training programs on anthropometric variables, physiological and muscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
1
2
0
Order By: Relevance
“…Additionally, fasting serum glucose as well as insulin resistance index were improved. 25 Mezghani et al, (2022) 26 Moreover, the outcome of our study came in accordance with Ghanbari-Niaki et al, (2013) 30 who examined the impact of pyramidal training on plasma lipid profile of sedentary participant. They found that when comparing the training group to the control group, there was a statistically significant reduction in total cholesterol, LDL density, in addition to blood viscosity.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, fasting serum glucose as well as insulin resistance index were improved. 25 Mezghani et al, (2022) 26 Moreover, the outcome of our study came in accordance with Ghanbari-Niaki et al, (2013) 30 who examined the impact of pyramidal training on plasma lipid profile of sedentary participant. They found that when comparing the training group to the control group, there was a statistically significant reduction in total cholesterol, LDL density, in addition to blood viscosity.…”
Section: Discussionsupporting
confidence: 87%
“…These findings were independent of weight loss or changes in body composition. Similarly, a recent RCT 89 that conducted three combined aerobic and resistance training programs, with different intensities of aerobic training (moderate-, high- intensity training group, and alternated-intensity training group) for 12 weeks found that the insulin sensitivity (assessed by HOMA-IR and QUICKI indices) decreased in the three training groups, with greater magnitude of improvement observed by the moderate-intensity training group. Furthermore, the volume of resistance training needed to improve glucose metabolism markers remains uncertain, particularly when resistance training is combined with aerobic training 90 .…”
Section: Discussionmentioning
confidence: 87%
“…There is another aspect to consider in the broader perspective. In general, standardized exercise programs used in research are designed to study the effects of physical activity on specific anthropometric and physiological variables [47][48][49][50] . In contrast, the joint exercise program from the Swedish Working Dog Association was originally designed to increase outdoor physical activity in dog owners and dogs, thereby improving health and wellbeing and promoting sustainable lifestyle changes in both parties 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that pronounced effects on body composition are not to be expected from exercise interventions without caloric restrictions 47 49 . Even so, there are contrasting studies that do in fact show substantial reductions of BMI and other body measurements as a result of isolated exercise interventions 50 52 . However, these studies are generally based on obese populations and exercise interventions lasting 12–14 weeks.…”
Section: Discussionmentioning
confidence: 99%